Tumour necrosis factor-α, interleukin-2 soluble receptor and different inflammatory parameters in patients with rheumatoid arthritis - Tânia Silvia Fröde; Patrícia Tenconi; Marilei Reynaud Debiasi; Yara Santos Medeiros (Hindawi Limited, 2002)
Background and aims: Although the participation of cytokines in the pathogenesis of rheumatoid arthritis (RA) seems to be unequivocal, their relationship with current serum markers of this disease is not clear. The present study analyses whether there is any correlation between the levels of tumour necrosis factor-α (TNF-α), interlukin-2 soluble receptor (sIL-2R) and the concentrations of C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and β2-microglobulin in a group of 21 patients with RA, all rheumatoid factor positive.